Factors Affecting Profit Persistence: Faktor-Faktor yang Mempengaruhi Persistensi Laba - Fibrianti Khoirunnisa’; Eny Maryanti (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the factors that influence earnings persistence in G0-Public BUMN companies listed on the Indonesian stock exchange for the 2017-2019 period. This study uses quantitative research with secondary data as a data source. The population of this study is the G0-Public BUMN companies listed on the Indonesia Stock Exchange for the 2017-2019 period, totaling 20 companies. Based on purposive sampling criteria obtained 16 companies that meet the research criteria. This study uses data analysis testing software SPSS (Statistical Package for Social Science) version 23. The results showed that operating cash flow, debt level, firm size, cash flow volatility, sales volatility had an effect on earnings persistence. Highlights: Earnings persistence in G0-Public BUMN companies: This study focuses on understanding the factors that influence the stability and consistency of earnings in government-owned public companies listed on the Indonesian stock exchange. Factors affecting earnings persistence: The study identifies several key factors that have an impact on earnings persistence, including operating cash flow, debt level, firm size, cash flow volatility, and sales volatility. Quantitative research and data analysis: The study adopts a quantitative research approach using secondary data obtained from the Indonesian stock exchange. Data analysis is performed using SPSS software to determine the relationships between the identified factors and earnings persistence. Keywords: earnings persistence, G0-Public BUMN companies, Indonesian stock exchange, quantitative research, SPSS.